eCM 2015
DOI: 10.22203/ecm.v030a13
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the Odontogenic ameloblast-associated gene affects the integrity of the junctional epithelium and gingival healing

Abstract: Odontogenic ameloblast-associated (ODAM) belongs to the secretory calcium-binding phosphoprotein (SCPP) gene cluster. It is expressed by the epithelial ameloblasts during the accrued mineralisation of enamel and by cells of the junctional epithelium (JE), a specialised portion of the gingiva that plays a critical role in periodontal health. In both cases, ODAM localises at the interface between the cells and the tooth surface. It is also present among the cells of the JE, and is distinctively highly expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 18 publications
(35 reference statements)
0
34
0
Order By: Relevance
“…The function of ODAM might be related to dentogingival attachment [5][6][7]. In this study, the value of ODAM in GCF was increased in deep periodontal pockets.…”
Section: Discussionmentioning
confidence: 50%
“…The function of ODAM might be related to dentogingival attachment [5][6][7]. In this study, the value of ODAM in GCF was increased in deep periodontal pockets.…”
Section: Discussionmentioning
confidence: 50%
“…In a recent publication, Wazen et al (2015) reported that teeth were erupted in ODAM KO mice. However, this is not contradictory to our observations because our results indicated that ODAM is not an essential gene for osteogenesis; i.e., without ODAM, osteogenesis can still occur.…”
Section: Discussionmentioning
confidence: 99%
“…Tissues were post-fixed in 1% osmium tetroxide/1.5% potassium ferrocyanide for 2 h on ice, dehydrated through an increasing concentration of acetone, and infiltrated and embedded in Epon resin. Preparation of ultrathin sections and imaging were essentially as described previously [34]. Low magnification micrographs from wild type and knockin mice ( n  = 3) were visually inspected to have comparable tissue architecture.…”
Section: Methodsmentioning
confidence: 99%